DEA-BSC and Diamond Performance to Support Museum Management - Antonella Basso; Stefania Funari (Mathematics, 2020)
In the present paper, we propose some models for the computation of an overall indicator which measures the performance of a set of museums from a multidimensional point of view. One of the most used methodologies that provide a multiple input–multiple output performance score is Data Envelopment Analysis (DEA), which in recent years has also been applied to museums. Recently, the literature on museums performance has proposed a model that combines DEA with the Balanced Scorecard (BSC) approach, which is used in the management control of organisations and focuses on a multidimensional framework based on four different dimensions of the organisation management. In the present contribution, we propose a two-stage DEA-BSC model which adopts more plain DEA models without weight restrictions and can be better understood by museums’ managers. In addition, in order to overcome the drawback of the low discriminatory power shown by this model when applied to a few museums, we propose some alternative ways to compute the overall performance at the second stage. One indicator computes the area of a special geometric representation of the efficiency scores obtained at the first stage for the four BSC perspectives and for this reason is named diamond efficiency. Finally, the models proposed are applied to the set of municipal museums of Venice.